Declining HIV prevalence among young pregnant women in Lusaka, Zambia - Elizabeth M Stringer; Namwinga T Chintu; Jens W Levy; Moses Sinkala; Benjamin H Chi; Jubra Muyanga; Marc Bulterys; Maximilian Bweupe; Karen Megazzini; Jeffrey SA Stringer (The World Health Organization, 2008)
OBJECTIVE: HIV prevention has been ongoing in Lusaka for many years. Recent reports suggest a possible decline in HIV sero-incidence in Zambia and some neighbouring countries. This study aimed to examine trends in HIV seroprevalence among pregnant and parturient women between 2002 and 2006. METHODS: We analysed HIV seroprevalence trends from two Lusaka sources: (i) antenatal data from a city-wide programme to prevent mother-to-child HIV transmission, and (ii) delivery data from two anonymous unlinked cord-blood surveillances performed in 2003 and again in 2005-2006, where specimens from > 97% of public-sector births in each period were obtained and analysed. FINDINGS: Between July 2002 and December 2006, the Lusaka district tested 243 302 antenatal women for HIV; 54 853 (22.5%) were HIV infected. Over this period, the HIV seroprevalence among antenatal attendees who were tested declined steadily from 24.5% in the third quarter of 2002 to 21.4% in the last quarter of 2006 (P < 0.001). The cord-blood surveillances were conducted between June and August 2003 and again between October 2005 and January 2006. Overall HIV seroprevalence declined from 25.7% in 2003 to 21.8% in 2005-2006 (P = 0.001). Among women < 17 years of age, seroprevalence declined from 12.1% to 7.7% (P = 0.015). CONCLUSION: HIV seroprevalence appears to be declining among antenatal and parturient women in Lusaka. The decline is most dramatic among women < " 17 years of age, suggesting a reduction in sero-incidence in this important age group.